2020
DOI: 10.1038/s41598-020-61003-4
|View full text |Cite
|
Sign up to set email alerts
|

Acute effects of ambient PM2.5 on lung function among schoolchildren

Abstract: Previous studies have found that fine particulate matter (PM2.5) air pollution is associated with decreased lung function. However, most current research focuses on children with asthma, leading to small sample sizes and limited generalization of results. The current study aimed to measure the short-term and lag effects of PM2.5 among school-aged children using repeated measurements of lung function.This prospective panel study included 848 schoolchildren in Zhejiang Province, China. Each year from 2014–2017, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 21 publications
2
24
0
Order By: Relevance
“…Among various air pollutants, particulate matter (PM), because of their small particle size, is the most harmful and most representative pollutant [8,9] and its major toxicological effects on human health and the environment have been observed for decades [10]. PM has been associated with an increased risk of respiratory health outcomes among children [11,12] and an increased risk of cardiovascular diseases, including heart failure and myocardial infarction, hypertension and stroke [13]. Children are a particularly vulnerable group to the effects of PM [14], as they are more active, breathe proportionately more air than adults, their respiratory systems are still developing, and they spend more time outdoors, inhaling the highest PM concentrations just above the ground.…”
Section: Introductionmentioning
confidence: 99%
“…Among various air pollutants, particulate matter (PM), because of their small particle size, is the most harmful and most representative pollutant [8,9] and its major toxicological effects on human health and the environment have been observed for decades [10]. PM has been associated with an increased risk of respiratory health outcomes among children [11,12] and an increased risk of cardiovascular diseases, including heart failure and myocardial infarction, hypertension and stroke [13]. Children are a particularly vulnerable group to the effects of PM [14], as they are more active, breathe proportionately more air than adults, their respiratory systems are still developing, and they spend more time outdoors, inhaling the highest PM concentrations just above the ground.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is only particulate matter below 5 micrometres which is able to reach the alveoli and pass into the bloodstream, which renders increased levels of PM2.5 in environments such as schools particularly concerning. Several studies have found that increased levels of PM2.5 can lead to a direct reduction of lung function, as well as indicate early lung disease in school children (4,5). There has also been an increased focus on finer particles, such as PM1, which are similarly able to penetrate the lungs and alveoli, and enter the bloodstream.…”
Section: Introductionmentioning
confidence: 99%
“…Among various air pollutants, particulate matter (PM) is the most harmful and most representative pollutant [8,9] and whose major toxicological effects on human health and the environment have been observed for decades [10]. PM has been associated with increased risk of respiratory health outcomes among children [11,12] and an increased risk of cardiovascular diseases, including heart failure and myocardial infarction, hypertension and stroke [13]. Children are a group particularly vulnerable to the effects of PM [14], as they are more active, breathe proportionately more air than adults, their respiratory systems are still developing, and they spend more time outdoors, inhaling the highest PM concentrations just above the ground.…”
Section: Introductionmentioning
confidence: 99%